Bufalin suppresses ovarian cancer cell proliferation via EGFR pathway. Issue 4 (20th February 2022) - Dou, Lei; Zou, Dan; Song, Feiran; Jin, Yuxin; Li, Yin; Zhang, Yi
Abstract: Background: Previous studies have shown that bufalin exerts antitumor effects through various mechanisms. This study aimed to determine the antineoplastic mechanism of bufalin, an extract of traditional Chinese medicine toad venom, in ovarian cancer. Methods: The 3-(4, 5-Dimethyl-2-thiazolyl)-2, 5-diphenyl tetrazolium bromide (MTT), 5-ethynyl-2′-deoxyuridine (EdU), and colony formation assays were used to investigate the antiproliferative effect of bufalin on the ovarian cancer cell line SK-OV-3. Molecular docking was used to investigate the combination of bufalin and epidermal growth factor receptor (EGFR) protein. Western blotting was performed to detect the expression of EGFR protein and its downstream targets. Results: Bufalin inhibited the proliferation of SK-OV-3 cells in a dose- and time-dependent manner. Bufalin was confirmed to combine with EGFR protein using molecular docking and downregulate expression of EGFR. Bufalin inhibited phosphorylation of EGFR, protein kinase B (AKT), and extracellular signal-regulated kinase (ERK). Conclusion: Bufalin suppresses the proliferation of ovarian cancer cells through the EGFR/AKT/ERK signaling pathway.